Selection of Multi-Criteria-Based Muhammadiyah Da'wah Strategy: A Comparative Study of Digital, Educational, and Social Da'wah - Harman, Rika; Nofriadi, Nofriadi (-, 2025)
In Muhammadiyah's efforts to spread the values of Islam Berkemajuan, an effective da'wah strategy is essential. In this study, the Analytical Hierarchy Process (AHP) method was used to determine the best da'wah strategy. In this analysis, three main criteria were used: Alignment with Muhammadiyah Values (KNM), Effectiveness of Delivery (EP), and Ease of Implementation (KI). Alternative da'wah strategies analyzed include Digital Da'wah (DD), Educational Da'wah (DP), and Social Da'wah (DS). The results of the Analytical Hierarchy Process (AHP) calculation show that the criterion with the highest value is Alignment with Muhammadiyah Values (0.5075), followed by Delivery Effectiveness (0.24). The results of the strategy prioritization step are as follows: Dakwah Pendidikan (DP) received the highest weight of 0.5075, while Dakwah Digital (DD) received a weight of 0.2473, and Dakwah Sosial (DS) received the lowest weight of 0.2452. Therefore, Educational Da'wah (DP) becomes the most recommended strategy as it has the highest weight, indicating that the educational method is more in line with Muhammadiyah's values and more effective in implementation. Based on these findings, Muhammadiyah is advised to strengthen the role of education as the main strategy in da'wah, while still optimizing the use of digital technology to increase the effectiveness of message delivery.